Peran Mata Pelajaran Aqidah Akhlak sebagai Media Efektif Penanaman Nilai-Nilai Karakter Siswa di Madrasah Ibtidaiyah Muhammadiyah Bolon - Sayidah, Aminatus; Subando, Joko (Lembaga Yasin AlSys, 2025)
Character education from an early age through religious instruction plays a strategic role in shaping students’ personalities, particularly at the elementary level, such as in Madrasah Ibtidaiyah. This study aims to describe and analyze the function of the Aqidah Akhlak subject as an effective means of instilling character values in students at Madrasah Ibtidaiyah Muhammadiyah Bolon. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings indicate that the Aqidah Akhlak subject significantly contributes to students’ character formation, particularly in the areas of honesty, responsibility, discipline, and mutual respect. This effectiveness is reinforced by the use of contextual teaching methods, teacher role modeling, and the integration of character values into each lesson. In conclusion, Aqidah Akhlak serves as a vital instrument for the continuous development of student character within the madrasah educational environment.